Analisis Kinerja Keuangan Anggaran Pendapatan dan Belanja Lembang (APBL) di Lembang Burasia Kecamatan Bittuang Kabupaten Tana Toraja - Wandy Desry; Elisabet Pali; Stefani M. Palimbong (Jurnal Bintang Manajemen, 2023)
Lembang Financial Performance Analysis is a form of accountability and a manifestation of financial decentralization and authority from the center to lembang. A lembang that is able to manage its finances effectively and efficiently is certainly expected to be able to stimulate the economy through absorption of the budget in productive and potential sectors so that overall it will be able to increase efficiency. In this study, efficiency ratio analysis is used to see how far the Lembang Burasia Government is in managing its regional finances. The results of the calculation of regional financial efficiency ratios average 120%.